Adaptasi Model Pembelajaran Tutorial Online UT pada Masa Pembelajaran Darurat Covid-19 - Athiyah Salwa (LPPM Universitas Terbuka, 2020)
The Covid-19 outbreak today changes a lot in the way teaching and learning progress in Indonesia. In most parts of the country, teachers still use the traditional ways to transfer knowledge from the collaboration of the conventional means of learning such as textbooks, boards, and situated in a classroom. In this pandemic situation, Government proposes that all teaching and learning activities in the schools should be conducted online. It makes stakeholders of education sectors, especially primary and secondary, manage learning strategies and systems. Based on the situation, Universitas Terbuka as the pioneer of open learning system has one program to facilitate students come from different places all around. It has an online tutorial where students can access material not only from the textbook but also supplementary materials such as teacher’s tutorial video, online tasks and exercises, and also online assessment. This kind of system can be adapted for traditional schools in the Pandemic era so that learning loss will not happen since students and teachers can still get connected to achieve learning goals. This article describes how the online tutorial UT can be implemented for primary, secondary, and even higher education in the Pandemic era to replace the traditional learning systems.